Signifikansi Tata Liturgi terhadap Keterlibatan Umat Menghadirkan Pembaharuan Hidup di Generasi Masa Kini - Rusmanto, Ayub; Gozaly, Ricky; Naftali, Joseph (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Abstract: Liturgy is a procedure of worship agreed upon and carried out by the church with the aim of worship in the church running smoothly and structured. The significance of liturgy in Christianity manifests God's encounter with the people so that the role of the church in facilitating the liturgy of worship involves the people presenting the renewal of the life of today's generation. The renewal of the lives of the younger generation as concrete evidence is carried out in worship to celebrate and be grateful for the work of salvation that God has done. Ironically, some churches today do not carry out liturgy well. The church does not facilitate well the "encounter" of God with the people through the liturgy of worship. Traditional churches maintain rigid liturgies, which do not suit the tastes of today's generation. The church also prefers seniors to be involved in the ministry. This results in people not feeling God's presence when they worship. This is experienced by today's generation so that they do not experience life renewal. Thus, the researcher focuses on researching the significance of the liturgy in the involvement of the people to bring renewal to the lives of today's generation. This paper aims to find out the impact of the liturgy and the involvement of the people to bring renewal to the lives of today's generation. The writing method used is a qualitative method using a survey. The results show that liturgy and the involvement of the people play an important role in the renewal of the lives of today's generation. Abstrak: Liturgi adalah tata cara ibadah yang disepakati dan dilakukan oleh gereja dengan tujuan peribadahan di gereja berjalan lancar dan terstruktur. Signifikansi liturgi dalam kekristenan memanifestasikan perjumpaan Allah dengan umat sehingga peran gereja dalam memfasilitasi liturgi ibadah melibatkan umat menghadirkan pembaharuan hidup generasi masa kini. Pembahruan hidup generasi muda sebagai bukti nyata dilakukan dalam ibadah untuk merayakan dan mensyukuri karya keselamatan yang Allah lakukan. Ironisnya, beberapa gereja masa kini tidak menjalankan liturgi dengan baik. Gereja tidak memfasilitasi dengan baik dalam “perjumpaan” Allah dengan umat melalui liturgi ibadah. Gereja tradisional tetap kokoh mempertahankan liturgi kaku, yang tidak sesuai dengan selera generasi masa kini. Gereja juga lebih memilih para senior untuk terlibat dalam pelayanan. Hal ini menyebabkan umat tidak merasakan hadirat Allah ketika beribadah. Hal ini dialami oleh generasi masa kini sehingga tidak mengalami pembaharuan hidup. Dengan demikian, peneliti berfokus pada penelitian signifikansi liturgi keterlibatan umat menghadirkan pembaharuan hidup generasi masa kini. Tulisan ini bertujuan untuk mengetahui dampak dari liturgi dan keterlibatan umat untuk menghadirkan pembaharuan hidup generasi masa kini. Metode penulisan yang digunakan adalah metode kualitatif dengan menggunakan survei. Hasil penelitian menunjukkan bahwa liturgi dan keterlibatan umat, berperan penting dalam pembaharuan hidup generasi masa kini.